In vitro study on efficacy of SKF7®, a Malaysian medicinal plant product against SARS-CoV-2 - Mohd Ridzuan Mohd Abd Razak; Nur Hana Md Jelas; Nor Azrina Norahmad; Norazlan Mohmad Misnan; Amirrudin Muhammad; Noorsofiana Padlan; Muhammad Nor Farhan Sa'at; Murizal Zainol; Ami Fazlin Syed Mohamed (BMC, 2024)
Abstract Background In early 2020, COVID-19 pandemic has mobilized researchers in finding new remedies including repurposing of medicinal plant products focusing on direct-acting antiviral and host-directed therapies. In this study, we performed an in vitro investigation on the standardized Marantodes pumilum extract (SKF7®) focusing on anti-SARS-CoV-2 and anti-inflammatory activities. Methods Anti-SARS-CoV-2 potential of the SKF7® was evaluated in SARS-CoV-2-infected Vero E6 cells and SARS-CoV-2-infected A549 cells by cytopathic effect-based assay and RT-qPCR, respectively. Target based assays were performed on the SKF7® against the S1-ACE2 interaction and 3CL protease activities. Anti-inflammatory activity of the SKF7® was evaluated by nitric oxide inhibitory and TLR2/TLR4 receptor blocker assays. Results The SKF7® inhibited wild-type Wuhan (EC50 of 21.99 µg/mL) and omicron (EC50 of 16.29 µg/mL) SARS-CoV-2 infections in Vero-E6 cells. The SKF7® also inhibited the wild-type SARS-CoV-2 infection in A549 cells (EC50 value of 6.31 µg/mL). The SKF7® prominently inhibited 3CL protease activity. The SKF7® inhibited the LPS induced-TLR4 response with the EC50 of 16.19 µg/mL. Conclusions In conclusion, our in vitro study highlighted anti-SARS-CoV-2 and anti-inflammatory potentials of the SKF7®. Future pre-clinical in vivo studies focusing on antiviral and immunomodulatory potentials of the SKF7® in affecting the COVID-19 pathogenesis are warranted.